Kajian Penanganan Pascapanen Rumput Laut Eucheuma cottonii di Kecamatan Mawasangka Kabupaten Buton Tengah - Nurdin, Iin Nurdiyanty (Agrisurya, 2024)
Post-harvest handling of seaweed is often ignored, while the quality of post-harvest raw materials is one the part that determines the quality of the final product. This research aims to examine the post-harvest handling process of Eucheuma cottonii seaweed in Central Buton Regency, Southeast Sulawesi. The research was conducted using a survey method by interviewing seaweed cultivators and collectors. Data analysis was carried out descriptively qualitatively. The results of the research show that post-harvest handling of quality improvement at the farmer and collector level still lacks attention to procedures for using equipment, weighing, packaging, labeling and storage (warehousing). The drying method used is in accordance with Indonesian National Standards. One of the reasons for the low post-harvest quality is the farmers' low understanding regarding the importance of handling seaweed on the price and quality of the final product produced. Therefore, the role of a supporting sub system is needed to be able to provide educational to the upstream sub system at the farmer level and the seaweed handling and processing sub system. Key words: Seaweed, post-harvest, quality, handling